The Effects of Three Different Assessment Types on Text Revisions: A Study of Indonesian EFL Learners - Andri Suherman (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This research article aimed at exploring the effects of three different assessments (self-, peer-, and teacher-) on students’ text revision. Ten Indonesian tertiary-level EFL students participated in this study. It investigated the extent to which three types of assessment facilitate text revision, and analyzed students’ perception of these assessments. The research methods used were students’ text revision and semi-structure interview. The findings revealed two main points. First, the results showed that students made the total of 2,096 revision changes across 40 drafts, with lower percentage of self-feedback incorporated into their revision. Furthermore, the findings indicated that students had a tendency to engage in self-assessment practice more often when revising their drafts. Second, students mostly appreciated teacher-assessment, as opposed to under half of them favoured peer-assessment. In contrast, self-assessment showed a balanced response between positive and negative comments. The implications of this study were provide practical insight to EFL teachers into how three assessment types (teacher-, peer-, and self-) can be developed to help improve students’ writing performance, and to inform EFL teachers with some suggestions to explore students’ perceptions regarding the three assessments to help facilitate quality-enhancing text revisions.